The Bible in American life - Goff, Philip; Farnsley, Arthur E.; Thuesen, Peter J. (Oxford University Press, 2017)
The Bible in American life today / by Philip Goff, Arthur Farnsley, and Peter Thuesen -- America's first Bible : native uses, abuses, and re-uses of the Indian Bible of 1663 / by Linford D. Fisher -- The debate over prophetic evidence for the authority of the Bible in Cotton Mather's Biblia Americana / by Jan Stievermann -- Navigating the loss of interpretive innocence : reading the enlightenment Bible in early modern America / by Robert E. Brown -- Reading the Bible in a Romantic era / by Beth Schweiger -- The origins of whiteness and the black (biblical) imagination : the Bible in the slave narrative tradition / by emerson B. Powery -- Biblical women in the woman's exponent : the Bible in nineteenth-century Mormonism / by Amy Easton-Flake -- Scriptualizing religion and ethnicity : the circle seven Koran / by Sylvester Johnson -- Reading the Bible in war and crisis to know the future / by Matthew Avery Sutton -- Reference bibles and interpretive authority / by B.M. Pietsch -- The soul's train : the Bible and southern folk and popular music / by Paul Harvey -- Where two or three are gathered : the adult Bible class movement and the social life of Scripture / by Christopher D. Cantwell -- The word is true : King James onlyism and the quest for certainty in American evangelical life / by Jason A. Hentschel -- Selling trust : the Living Bible and the business of biblicism / by Daniel Vaca -- The Bible and the legacy of first wave feminism / by Claudia Setzer -- Let us be attentive : the orthodox study Bible, converts, and the debate on orthodox lay uses of Scripture / by Garrett Spivey -- The continuing distinctive role of the Bible in American lives : a comparative analysis / by Corwin Smidt -- Emerging trends in American children's Bibles, 1990-2015 / by Russell W. Dalton -- The curious case of the Christian Bible and the U.S. Constitution : challenges for educators teaching the Bible in a multi-religious context / by John F. Kutsko -- Transforming practice : American Bible reading in digital culture / by John B. Weaver -- Readers and their e-bibles : the shape and authority of the hypertext canon / by Bryan Bibb -- How American women and men read the Bible / by Amanda Friesen -- Feels right exegesis : qualitative research on how millennials read the Bible / by J. Derrick Lemons -- Crowning the King : the use of production and reception studies to determine the most popular English-language Bible translation in contemporary America / by Paul Gutjahr -- Literalism as creativity : intertextuality in making a biblical theme park / by James S. Bielo -- The Bible in the evangelical imagination / by Daniel Silliman -- Feeling the word : sensing Scripture at Salvation Mountain / by Sara M. Patterson -- The Bible : then and now / by Mark Noll
Keywords: Bible -- Criticism, interpretation, etc -- United States; Bible -- Study and teaching -- United States; Bible -- Reading -- United States; Bible -- Publication and distribution -- United States; Bible -- Influence; United States -- Religion; Aufsatzsammlung; Konferenzschrift -- 2014 -- Indianapolis, Ind.; Geschichte 1650-2015; Alltag; Frömmigkeit; Religiosität; Bibellektüre; USA; Kulturelle Identität; Religiöse Identität; Rezeption; Bibel